Prognostic value of systemic immune-inflammation index for patients undergoing radical prostatectomy: a systematic review and meta-analysis - Chen, Zhan; Zhang, Yao; Chen, Wei (Frontiers in Immunology, 2025)
ObjectiveThe prognostic value of the systemic immune-inflammation index (SII) for prostate cancer (PCa) patients receiving different treatments remains unclear. This research examined the relevance of SII in individuals undergoing radical prostatectomy (RP).MethodsPubMed, Embase, Web of Science, Cochrane, Wanfang, and China National Knowledge Infrastructure (CNKI) dat3 abases were used to search literature up to May 2024. The quality was evaluated with Newcastle-Ottawa Scale. Outcomes examined were associations between SII and overall survival (OS), biochemical recurrence-free survival (BFS), and cancer-specific survival (CSS). Pooled analysis, Egger’s test, and sensitivity analysis were conducted using Review Manager 5.4.1 and Stata 15.1. The GRADE system was employed to evaluate and grade the evidence for each outcome. Subgroup analyses were performed for outcomes with significant heterogeneity to evaluate the possible confounders, if data were sufficient.ResultsOut of 101 identified studies, eight studies involving 8,267 individuals were included. Patients with higher SII had shorter overall survival (HR: 1.89; 95% CI: 1.31-2.71; P = 0.0006), biochemical recurrence-free survival (HR: 1.55; 95% CI: 1.08-2.22; P = 0.02), and cancer-specific survival (HR: 3.63; 95% CI: 1.66-7.94; P = 0.001). The evidence for OS and CSS was rated very low-quality due to serious heterogeneity and/or imprecision. The prognostic value of SII for BFS was rated as low-quality evidence, given no serious risk observed. Subgroup analysis showed that, except for the subgroup aged >65 years (HR: 3.70; 95%CI: 0.91, 15.06, P=0.07), the prognostic value of SII for OS was not significant, but the prognostic value of SII for OS in other subgroups was still significant.ConclusionsHigh SII was linked to shorter OS, BFS, and CSS in patients undergoing RP. However, the quality of the evidence provided by this study was low.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024558431.